SALT-II : a balance of ambivalences - Bilgrami, Jafar Raza, 1939- (Intellectual Pub. House : sole distributors, Intellectual Book Corner, 1981)
On the Strategic Arms Limitation Treaty (SALT), under consideration between the U.S.A. and U.S.S.R.